Early Lactate Clearance Rate is an Indicator of Outcome in Severe Sepsis and Septic Shock - Sultana, Rozina; Hamid, Tarikul; Ahsan, ASM Areef; Fatema, Kaniz; Ahmed, Fatema; Saha, Debasish Kumar; Saha, Madhurima; Nazneen, Suraiya; Islam, Ariful (BIRDEM Medical Journal, 2018)
Background: Lactate clearance is an important marker of global tissue hypoxia and might be used as an indicator of outcome in patients with severe sepsis and septic shock. This study was done to see the association between lactate clearance with the outcome of the patients of severe sepsis and septic shock among the patients who were admitted in the Department of Critical Care Medicine of BIRDEM General Hospital. Methods: This observational study was done in the Department of Critical Care Medicine, BIRDEM General Hospital from August 2015 to July 2016. At zero hour (during admission), first sample of serum lactate was sent and second sample after 6 hours of resuscitation for calculation of lactate clearance rate. Patients having lactate clearance e”10% were classified as high lactate clearance (HLC) and <10% were low lactate clearance (LLC). Results: Total 186 patients (male 96, female 90, mean age 63.07±14.17 years) with severe sepsis (80) and septic shock (106) were enrolled. Diabetes mellitus (DM) was the most common co morbidity (76.9%) and predominant diagnosis was pneumonia (90.3%). Among patients with septic shock, 51.9% (55/106) had LLC and 48.1% (51/106) had HLC. Among patients with severe sepsis, 28.8% (23/80) had LLC and 71.2% (57/80) had HLC. Among 57 patients of HLC group of severe sepsis, 73.6% (n= 42) were survivors and 26.3% (n=15) were non-survivor and 23 patients of LLC group of severe sepsis, 26.09% (n=6) were survivors and 73.91% (n=17) were-non survivors (p=<0.001). Among 51 patients of HLC group of septic shock, 78.43% (n=40) were survivors and 21.57% (n=11) were non-survivors and 55 patients of LLC group of septic shock, 29.09% (n=16) were survivors and 70.91% (n=39) were non-survivors (p=<0.001). Conclusion: Patients with HLC after 6 hours of management had better outcome than LLC. Birdem Med J 2018; 8(3): 223-228